The feasibility of utilizing microwave-assisted pyrolysis for Albizia branches biomass conversion into biofuel productions - Abd, Maha Faisal; Al-Yaqoobi, Atheer Mohammed (International Journal of Renewable Energy Development, 2023)
The consumption of fossil fuels has caused many challenges, including environmental and climate damage, global warming, and rising energy costs, which has prompted seeking to substitute other alternative sources. The current study explored the microwave pyrolysis of Albizia branches to assess its potential to produce all forms of fuel (solid, liquid, gas), time savings, and effective thermal heat transfer. The impact of the critical parameters on the quantity and quality of the biofuel generation, including time, power levels, biomass weight, and particle size, were investigated. The results revealed that the best bio-oil production was 76% at a power level of 450 W and 20 g of biomass. Additionally, low power levels led to enhanced biochar production, where a percentage of 70% appeared when employing a power level of 300 W. Higher power levels were used to increase the creation of gaseous fuels in all circumstances, such as in 700 W, the gas yield was 31%. The density, viscosity, acidity, HHV, GC-MS, and FTIR instruments were used to analyze the physical and chemical characteristics of the bio-oil. The GC-MS analysis showed that the bio-oil consists of aromatic compounds, ketones, aldehydes, acids, esters, alkane, alkenes and heterocyclic compounds. The most prevalent component was aromatic compounds with 12.79% and ketones with 12.15%, while the pH of the oil obtained was 5, and the HHV was 19.5 MJ/kg. The pyrolysis productions could be promising raw materials for different applications after further processing.